2016
DOI: 10.1038/srep32665
|View full text |Cite
|
Sign up to set email alerts
|

High minimum inhibitory concentration of imipenem as a predictor of fatal outcome in patients with carbapenem non-susceptible Klebsiella pneumoniae

Abstract: Carbapenem resistance in Klebsiella pneumoniae is important because of its increasing prevalence and limited therapeutic options. To investigate the clinical and microbiological characteristics of patients infected or colonized with carbapenem non-susceptible K. pneumoniae (CnsKP) in Taiwan, we conducted a retrospective study at Taipei Veterans General Hospital from January 2012 to November 2013. Carbapenem non-susceptibility was defined as a minimum inhibitory concentration (MIC) of ≥2 mg/L for imipenem or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…The burden attributable to respiratory infections has been well-described in the literature; however, few studies have focused specifically on the impact of gram-negative respiratory C-NS infections in comparison with C-S infections, and there are no studies of which we are aware that have evaluated both clinical and economic outcomes and the resulting financial impact to the hospital. The in-hospital mortality rates reported here are broadly comparable to others in the literature, with previously reported rates ranging from 14.5% to 60.6% for C-NS isolates [14][15][16]23,24]. The highest mortality rate in this study (25.7%) was in patients with other conditions (a principal diagnosis other than bacterial pneumonia) who developed a concomitant respiratory infection during their hospital stay.…”
Section: Discussionsupporting
confidence: 85%
“…The burden attributable to respiratory infections has been well-described in the literature; however, few studies have focused specifically on the impact of gram-negative respiratory C-NS infections in comparison with C-S infections, and there are no studies of which we are aware that have evaluated both clinical and economic outcomes and the resulting financial impact to the hospital. The in-hospital mortality rates reported here are broadly comparable to others in the literature, with previously reported rates ranging from 14.5% to 60.6% for C-NS isolates [14][15][16]23,24]. The highest mortality rate in this study (25.7%) was in patients with other conditions (a principal diagnosis other than bacterial pneumonia) who developed a concomitant respiratory infection during their hospital stay.…”
Section: Discussionsupporting
confidence: 85%
“…A large-scale clinical study evaluating the risk factors of mortality and attributable mortality of TCRKP infections is needed. A recent study disclosed that a positive culture of CnSKP was associated with high in-hospital mortality, regardless of colonization or infection [28]. Patients with TCRKP colonization would also likely exhibit high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, patients who acquired CRE infections owing to KPC (dominant carbapenemase type)-producing Enterobacteriaceae also had a trend toward more fatal outcomes than those without KPC ( P = 0.14) ( Chang et al, 2015 ). An additional CRE study conducted at a single medical center of northern Taiwan during 2012–2013 showed that a CRE isolate with an imipenem MIC ≥ 16 mg/L independently predicted 14-day mortality among patients regardless if the isolate was from infection or colonization ( Wu et al, 2016 ). In the survey published by Wu et al, KPC-2 was the dominant (87.1%) carbapenemase among CPE (29.5% of overall CRE), and the in-hospital mortality rate among patients with CR- K. pneumoniae was 43.8% ( Wu et al, 2016 ).…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 99%
“…An additional CRE study conducted at a single medical center of northern Taiwan during 2012–2013 showed that a CRE isolate with an imipenem MIC ≥ 16 mg/L independently predicted 14-day mortality among patients regardless if the isolate was from infection or colonization ( Wu et al, 2016 ). In the survey published by Wu et al, KPC-2 was the dominant (87.1%) carbapenemase among CPE (29.5% of overall CRE), and the in-hospital mortality rate among patients with CR- K. pneumoniae was 43.8% ( Wu et al, 2016 ). Wang et al examined 1135 clinical isolates of various Enterobacteriaceae species collected from four major hospitals in Taiwan between 2010 and 2012.…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 99%